Integrating Mobile Technology in Teaching Physical Education - Miroslava R. Ristić (University of Belgrade, Teacher Education Faculty, 2018)
Mobile technologies are becoming significantly important in teaching Physical Education. It has been observed that they can contribute to the culture of healthy living (Palmárová & Lovászová, 2012), as well as to raising ecological awareness and developing a sustainable relationship with nature (Uzunboylu et al., 2009). Owing to cloud computing, mobile technologies are omnipresent, economical and user-friendly for both teachers and students, but still not sufficiently used for teaching purposes (Ristić, 2018). Their successful implementation in educational institutions for the purpose of creating a stimulating educational environment is becoming imperative, whereas the models of their use represent a challenge. Apart from the analysis of cloud computing service models and detection of educational potentials of mobile technologies, the aim of this paper is to analyse the mobile technology implementation models in teaching Physical Education. The paper represents a qualitative research which uses the modeling method, as well as the reinterpretation of the existing research. The conducted analyses show that mobile technologies can improve Physical Education teaching and that they can be integrated through the two-phase implementation process. This is not a fast and simple process. The findings indicate that our schools do not have the necessary level of e-maturity, and that Physical Education teachers do not obtain advanced digital competences during their initial education.